Molecular docking analysis of β-1,4-Glucosidase from trichoderma harzianum against mycelial cell wall components of macrophomina phaseolina - Mohammad Hood, Mohammad Hakim; Abdul Wahab, Roswanira; Tengku Abdul Hamid, Tengku Haziyamin; Abdul Hamid, Azzmer Azzar (2019)
The efficacy of β-1,4-glucosidase enzyme produced by Trichoderma harzianum in disrupting phytopathogenic fungus, Macrophomina phaseolina had been studied and recorded. Meanwhile, the molecular mechanisms underlying the cell wall components of M. phaseolina recognition remain elusive. Molecular docking was done using Autodock Vina 1.1.2 program to determine the binding location, and interactions formed between β-glucan and chitin with the residues of β-glucosidase. Docking simulation was done in two means, blind docking and specific docking which assigned the enzyme to be rigid with flexible ligands. The search space for specific binding was determined from the residues predicted by COACH tool. Respectively, the blind docking of chitin and of β-glucan showed binding affinity of -8.1 kcal/mol and -7.8 kcal/mol while in specific docking showed -7.8 kcal/mol and -7.7 kcal/mol. The low binding affinity indicated the binding between β-glucosidase and the ligands was favourable. Several residues were found in consensus to form up the pocket of active site. These include Ser183, Thr185, Phe186, Asn231, Phe256, Trp345, Glu373, Glu430 and Trp431. Glu373 was found to constantly form hydrogen bond with both ligands as this residue could be the nucleophile for hydrolysis. Hence, this finding provides a fundamental basis for improving biological agent in inhibiting the growth of the phytopathogenic fungus.